Sports and Disciplined Movement – Paths To Stimulating Strivings - Jesús Ilundáin Agurruza (Recerca: Revista de Pensament i Anàlisi, 2016)
The focus of this article is the relation between life, sport, and disciplined movement. How do these enhance life?  This means looking at sports in terms of the qualitative experiences they afford and considering the role of disciplined movement.  Phenomenological description helps explore the normative paths that heighten said experiences.  At their best, such paths result in skillful strivings to excel within communitarian frameworks, of which the Japanese practices of self-cultivation are exemplary.  Sheets-Johnstone’s forays into kinesthesia, Ortega y Gasset’s meditations, and Husserl’s historical lifeworld (lebenswelt) animate this account. The aim is to show how sports and movement, in bridling an exuberant temperament, cultivate our abilities, creativity, and excellence, ultimately encouraging stimulating lives.